Risk Aversion is Associated with Decision Making among Community-Based Older Persons - Boyle, Patricia; Yu, Lei; Buchman, Aron; Bennett, David (Frontiers in Psychology, 2012)
Background: Risk aversion is associated with many important decisions among younger and middle aged persons, but the association of risk aversion and decision making has not been well studied among older persons who face some of the most significant decisions of their lives. Method: Using data from 606 community-dwelling older persons without dementia from the Rush Memory and Aging Project, an ongoing longitudinal epidemiologic study of aging, we examined the association of risk aversion with decision making. Risk aversion was measured using standard behavioral economics questions in which participants were asked to choose between a certain monetary payment ($15) versus a gamble in which they could gain more than $15 or gain nothing; potential gamble gains ranged from $20 to $300 with the gain amounts varied randomly over questions. Decision making was measured using a 12 item version of the Decision Making Competence Assessment Tool. Findings: In a linear regression model adjusted for age, sex, education, and income, greater risk aversion was associated with poorer decision making (estimate=-1.03, standard error (SE)=0.35, p=0.003). Subsequent analyses showed that the association of risk aversion with decision making was independent of cognitive function. Conclusion: Greater risk aversion is associated with poorer decision making in advanced age and the effect of risk aversion on decision making is above and beyond that of cognition.